Demystifying Plagiarism In Academia - Ben Moussa Yasser; Bacher Ahmed (University of Eloued جامعة الوادي, 2025)
Plagiarism seems to be carried out across the board. Novice as well as expert academics are fully aware that this malpractice is unethical and severely condemned. Nonetheless, plagiarism does not appear to give way to academic honesty. The current paper endeavors to spot light on the issue by discussing its nature and point out to its consequences. It is within the range of the paper to examine the effectiveness of software programs in detecting plagiarism and expose perpetrators.
Article . Ex Professo. Vol. 10. N1
Keywords: plagiarism; Academics; software programs; perpetrors